EFFECT OF PEG LOADING ON THE MICROSTRUCTURE AND PHOTOCATALYTIC ACTIVITY OF TiO2 FILM ON CERAMIC TILE - Najwa, N.A.K.Z.; Juoi, J.M.; Rosli, Z.M.; Moriga, T. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
TiO2 films have been used and deposited on various substrates due to its potential application in photocatalysis. However, when deposited on ceramic substrates, TiO2 films commonly resulted in a cracked morphology of the film which lead to delamination and peel off of film from substrate. Therefore, a binder needs to be added into the composition of TiO2 solution in an effort to improve TiO2 film structure. In this work, polyethylene glycol 2000 (PEG2000) was added into TiO2 sol as an additive to act as a binder, in order to improve the microstructure of TiO2 films on unglazed ceramic tiles and glass substrate by sol-gel dip-coating. The crystalline phases were characterized by XRD, while film morphologies were analyzed by SEM. The photocatalytic activity was evaluated by degradation of methylene blue (MB) under UV-radiation. The use of PEG successfully eliminated cracks and delamination of TiO2 films even at the smallest amount of PEG added (1 mol%). Also, the addition of PEG creates pores on the surface of the films. This contributes to a higher degradation of MB and enhanced photocatalytic activity. The best degradation of MB observed was at 3 mol% PEG due to bigger pores on the surface of the film.